Autophagy as a Vital Therapy Target for Renal Cell Carcinoma - He, Ying-hua; Tian, Guo (Frontiers in Pharmacology, 2021)
Autophagy, which degrades and recycles superfluous organelles or damaged cellular contents, plays a dual role in tumor including renal cell carcinoma (RCC). Many of autophagy-related proteins are regarded as prognostic markers of RCC. Noteworthily, research efforts have focused on promising RCC therapy compounds including synthetic and phytochemical autophagy modulators. In this review, we firstly highlight the importance of autophagy in RCC and the novel treatment for RCC based on the functions of autophagy.